Related Topics:

More Algebra Lessons, More Algebra Worksheets, More Algebra Games

**How to solve cubic equations using the Factor Theorem?**

In these lessons, we will consider how to solve cubic equations of the form

*px*^{3} + *qx*^{2} + *rx* + *s* = 0 where *p, q, r * and *s* are constants by using the Factor Theorem and Synthetic Division.

f(–1) = –2 + 3 + 11 – 6 ≠ 0

f(2) = 16 + 12 – 22 – 6 = 0

We find that the integer root is 2.

Step 2: Find the other roots either by inspection or by synthetic division.

**How to use the Factor Theorem to factor polynomials?**

1) Factor P(x) = 3x^{3} − x^{2} − 10x + 8

1) Factor P(x) = 2x^{3} − 9x^{2} + x + 12
**What are The Remainder Theorem and the Factor Theorem?**

How to use the Theorems to find the linear factorization of a polynomial?

Factor F(x) = 2x^{3} − 3x^{2} − 5x + 6

**How to use the Factor Theorem to solve a cubic equation?**

Solve the equation 2x^{3} −5x^{2} − 10 = 23x
How to solve a cubic equation?

How to solve Cubic Equations using the Factor theorem and Long Division?

Solve the cubic equation 2x^{3} − 6x^{2} + 7x − 1 = 0
Solving a Cubic Equation

3x^{3} −4x^{2} − 17x = x^{3} + 3x^{2} − 10

You can use the free Mathway widget below to practice Algebra or other math topics. Try the given examples, or type in your own problem and check your answer with the step-by-step explanations.

More Algebra Lessons, More Algebra Worksheets, More Algebra Games

In these lessons, we will consider how to solve cubic equations of the form

**Example:**

Find the roots of f(*x*) = 2x^{3} + 3*x*^{2} – 11*x* – 6 = 0, given that it has at least one integer root.

**Solution:**

Since the constant in the given equation is a 6, we know that the integer root must be a factor of 6. The possible values are

Step 1: Use the factor theorem to test the possible values by trial and error.

f(1) = 2 + 3 – 11 – 6 ≠ 0f(–1) = –2 + 3 + 11 – 6 ≠ 0

f(2) = 16 + 12 – 22 – 6 = 0

We find that the integer root is 2.

Step 2: Find the other roots either by inspection or by synthetic division.

2x^{3} + 3*x*^{2} – 11*x* – 6

= (*x* – 2)(*ax*^{2} + *bx + c*)

= (*x* – 2)(2*x*^{2} + *bx + *3)

= (*x* – 2)(2*x*^{2} + 7*x + *3)

= (*x* – 2)(2*x* + 1)(*x* +3)

So, the roots are

** Example: **

Solve the cubic equation *x*^{3} – 7*x*^{2} + 4*x* + 12 = 0

** Solution: **

Let f(*x*) = *x*^{3} – 7*x*^{2} + 4*x* + 12

We find that f(–1) = –1 – 7 – 4 + 12 = 0

So, (*x* + 1) is a factor of f(*x*)

* **x*^{3} – 7*x*^{2} + 4*x* + 12

= (*x* + 1)(*x*^{2} – 8*x* + 12)

= (*x* + 1)(*x* – 2)(*x* – 6)

1) Factor P(x) = 3x

1) Factor P(x) = 2x

How to use the Theorems to find the linear factorization of a polynomial?

Factor F(x) = 2x

Solve the equation 2x

How to solve Cubic Equations using the Factor theorem and Long Division?

Solve the cubic equation 2x

3x

Rotate to landscape screen format on a mobile phone or small tablet to use the **Mathway** widget, a free math problem solver that **answers your questions with step-by-step explanations**.

You can use the free Mathway widget below to practice Algebra or other math topics. Try the given examples, or type in your own problem and check your answer with the step-by-step explanations.

We welcome your feedback, comments and questions about this site or page. Please submit your feedback or enquiries via our Feedback page.